Paracoccidioides lutzii Plp43 is an active glucanase with partial antigenic identity with P. brasiliensis gp43. - Natanael P Leitão; Milene C Vallejo; Palloma M Conceição; Zoilo P Camargo; Rosane Hahn; Rosana Puccia (Public Library of Science (PLoS), 2014)
Paracoccidioides brasiliensis and P. lutzii cause paracoccidioidomycosis (PCM). P. brasiliensis main diagnostic antigen is glycoprotein gp43, and its peptide sequence is 81% identical with a P. lutzii ortholog here called Plp43. P. lutzii ("Pb01-like") apparently predominates in Midwestern/Northern Brazil, where high percentages of false-negative reactions using P. brasiliensis antigens have recently been reported. The aim of this work was to produce recombinant Plp43 to study its antigenic identity with gp43.We expressed rPlp43 as a secreted major component in Pichia pastoris and studied its reactivity in immunoblot with PCM patients' sera from Southwestern and Midwestern Brazil.We showed that rPlp43 is not glycosylated and bears glucanase activity. The protein did not react with anti-gp43 monoclonal antibodies in immunoblot, suggesting absence of the corresponding gp43 epitopes. Nevertheless, common epitope(s) might exist, considering that gp43-positive PCM sera recognized rPlp43 in immunoblot, while gp43-negative sera (33 out of 51) from patients resident in Midwestern Brazil were also rPlp43-negative. Two genotyped P. lutzii were from patients with gp43-negative sera, suggesting that non-reactive sera are from patients infected with this species.Our data suggest that gp43 and Plp43 bear one or only a few common epitopes and that gp43 cannot be used in diagnosis of PCM patients infected with P. lutzii probably because Plp43 is poorly expressed during infection.